Single-center real-world data and technical considerations from 100 consecutive patients treated with the Perceval aortic bioprosthesis - Müller, Hannes; Szalkiewicz, Philipp; Benedikt, Peter; Ratschiller, Thomas; Schachner, Bruno; Schröckenstein, Sophie; Zierer, Andreas (Frontiers in Cardiovascular Medicine, 2024)
Although, the Perceval sutureless aortic valve bioprosthesis presents a feasible alternative to conventional aortic valve prostheses, the extent of its applicability with respect to technical considerations for a real-world patient collective is still under debate. One-hundred patients received the Perceval prosthesis (males: 59 [59]; age: 72.5 [7.3-79] years between 12/2015 and 02/2023,; EuroSCORE II: 2.8 [1.7-5.4]) for aortic valve replacement (AVR) with additional concomitant procedures, for underlying severe aortic valve stenosis (n= 93; [93]), endocarditis (n= 5 [5]) and redo AVR (n= 7; [7]), including prior surgical AVR (n= 4; [4]) and failed transcatheter aortic valve implantation (n= 3; [3]). Surgery was conducted primarily by median sternotomy (n= 71; [71]) and upper hemisternotomy approach (n=29; [29]) alternatively. Over a median follow-up time of 36.5 (16.5-53) months, eight patients (8%) underwent postoperative pacemaker implantation, with five (5%) due to high-grade atrioventricular block, while nine (9%) patients experienced stroke. The median values of maximum and mean gradients across all valve sizes were 22 (18-27.5) mmHg and 10 (13-18) mmHg, respectively. Two patients (2%) had moderate and one (1%) severe paravalvular leakage with the latter presenting the only case of underlying valve migration and induced redo AVR with valve explantation two days following initial surgery. Thirty-day (and overall mortality) was 5% and 26%, respectively. Implantation of Perceval bioprosthesis is feasible for a variety of indications, with excellent hemodynamic results and low complication rates in a real-world high-risk patient collective.